Stomach Content Analysis of Pterygoplichthys pardalis from The Air Hitam River, Payung Sekaki District, Riau Province - Mey Tisasari; Deni Efizon; Chaidir P Pulungan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Pterygoplichthys pardalis is a type of freshwater fish that live in the Air Hitam River, one of polluted river in Riau. Eventhough the river is polluted, but this species well developed in that river. To understand the stomach content of that fish and its relationship with size, sex and level of maturity, a study has been conducted from February to May 2015. There were 169 fishes captured, however only 91 fishes were used for stomach content study as the other had empty stomach. The stomach content was analyzed and was used as a basis to calculate the Preponderance Index (PI). Results shown that the main food of P. pardalis is Bacillariophyceae (PI 41.19%), small fishes (91-124 mm TL) tend to consume Cyanophyceae (PI53.54%), while the big fish (more than 295 mm TL) tend to consume Bacillariophyceae (PI 45,48%) and rest of crustacea (PI 46,66%). Male eat more Cyanophyceae (PI 46,69%), the female consume Bacillariophyceae (PI 39,05%). Fish with low maturity level (2nd and 3rd maturity level) tend to eat Chlorophyceae (PI 48.81%) and Bacillariophyceae (PI 34.19%), while the mature fish prefer to consume Chlorophyceae (PI 37.14%). Based on data obtained, it can be concluded that the main food of P. pardalis was various and it is related to body size, sex and gonad maturity level.Keywords : Pterygoplichthys pardalis, Stomach Content Analysis, Preponderance Index